A quality project for radiation reduction in the cath lab. Issue 1 (2nd January 2019) - de Ceuninck, Michel; Muyldermans, Philip; van de Walle, Stefaan; Bergez, Bernard; Haspeslagh, Rik; Stammen, Francis; Dujardin, Karl
Abstract: The radiation exposure in the cath lab of patients, cardiologists, and nurses was measured during three consecutive periods of 8 weeks. The first 8 weeks the baseline radiation exposure was obtained. In the second period standard incidences for coronarography and frame rate were changed, without compromising the image quality of the examination. In the third period, a pelvic shield covered the lower part of the patient. This pilot quality project demonstrates that further significant reduction in radiation exposure of 37% is possible for patients. A significant reduction in radiation exposure of 53 and 62% was obtained among cardiologists and nurses working in the cath lab, even with the already diminished radiation exposure over the last years by better equipment and general radioprotection measures.